Sorafenib-triggered radiation recall dermatitis: case report and literature review - Lin, Fang-Yi; Chang, Tung-Hao; Huang, Chia-Chun; Hung, Li-Chung; Chou, Tsai-Wei; Lin, Jhen-Bin (Therapeutic Radiology and Oncology, 2019)
Sorafenib-induced radiation recall dermatitis (RRD) is rare. Here we present a case of sorafenib- induced RRD previously irradiated for bone metastasis from hepatocellular carcinoma (HCC). The patient was an 86-year-old Taiwanese woman. Radiotherapy with 3,000 cGy in 10 fractions was delivered for her bone metastasis in palliative intention. A month after completion of irradiation, sorafenib 400 mg was administered orally twice daily. Pruritus occurred on the same day of initiated sorafenib, restricted to the previous irradiated skin, which progressed, one week after, to grade 1 pruritus, erythema, desquamation and hyperpigmentation of lower back without pain. (CTCAE v4.03) Topical steroid cream was prescribed without sorafenib adjustment. Her skin reaction resolved in several days later. To the best of our knowledge, this is the first case report of a female patient presenting sorafenib-triggered RRD. Our case report highlights the possibility in both genders and could provide more information for further understanding given its rarity. Clinicians should be alert to the possibility of RRD in patients with dermatologic reaction in previously irradiated skin after receiving sorafenib.